Prey selection in the trap-nesting wasp Trypoxylon (Trypargilum) opacum Brèthes (Hymenprtera; Crabronidae) - Buschini,MLT. (2010)
The purpose of our research was to document and discuss the temporal patterns of prey use shown by the trap-nesting wasp Trypoxylon opacum in two different habitats in Southern Brazil. It was carried out from December 2001 to December 2004. Twenty nine species belonging to five families of spiders were captured by T. opacum. Araneidae was the most captured family and has been strongly represented by the genus Eustala. Through Bray-Curtis´s coefficient and the unweighted pair group method average (UPGMA), the spiders can be divided into three groups: the smaller group includes the most abundant species (Alpaida sp2, Bertrana rufostriata, Eustala sp1, Eustala sp2, Eustala sp3 and Eustala sp4), the second group includes species with intermediate abundance (Alpaida, Alpaida gracia and Mangora sp2), and the third and largest group includes the less abundant species, (Acacesia villalobosi, Alpaida argenata, Alpaida sp1, Araneus blumenau, Araneus sicki, Crysometa boraceia, Crysometa sp3, Eustala sp8, Eustala sp11, Larinia t-notata, Mangora sp1, Ocrepeira aff gnomo, Sanogasta sp., Sanogasta sp2, Sanogasta sp3, Salticidae sp2, Theridion sp1, Theridion sp2, Wagneriana eupalaestris, Wagneriana iguape). Of 1,053 identified spiders, 362 were captured in the grassland areas and 691 in the swamp, since T. opacum built nests only in these two habitats. The diversity, richness and evenness of spiders in T. opacum nests were higher in grassland than in the swamp.